Variabilitas Musiman Dan Spasial Pengaruh ENSO Dan IOD Terhadap Curah Hujan Di Sumatera Barat (1994–2023) - Muhammad Aulia Zikri; Ferdy Indra Kurniawan; Rio Hansyen Saragih; Gracia Nadya Angelina Pangalo; Yosafat Donni Haryanto; Giarno (Pendidikan Geografi Universitas Muhammadiyah Prof. Dr. Hamka, 2026)
ENSO (El Nino-Southern Oscillation) and IOD (Indian Ocean Dipole) significantly impact weather variability in tropical regions, including Indonesia, which can influence rainfall patterns and potentially lead to hydrometeorological disasters. This study analyzes the influence of ENSO and IOD phenomena on rainfall patterns in West Sumatra through a quantitative approach. The research utilizes rainfall data from three meteorological stations in West Sumatra spanning 30 years (1994-2023). The study employs correlation analysis to examine the relationship between ENSO (using NINO 3.4 index) and IOD with rainfall patterns across different seasons. Results indicate that ENSO and IOD impacts vary significantly by season, with the strongest correlations observed during the SON (September-October-November) period. During this period, ENSO showed strong negative correlations (r = -0.59 to -0.62) at Minangkabau and Teluk Bayur stations, while IOD demonstrated strong positive correlations (r = 0.61 to 0.63). The research findings contribute to understanding climate variability in West Sumatra and can support local climate adaptation strategies and disaster mitigation planning